2017
DOI: 10.1002/jbm.a.36222
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of tough poly(ethylene glycol)/collagen double network hydrogels for tissue engineering

Abstract: In this study, a series of poly(ethylene glycol)/collagen (PEG/Col) double network (DN) hydrogel is fabricated from PEG and Col. Results of the compressive strength test indicate that the strength and toughness of these DN hydrogels are significantly enhanced. The fracture strength of PEG/ Col DN hydrogels increases by 9-to 12-fold compared with that of PEG single network (SN) hydrogel, and by 36-to 48-fold compared with that of Col SN hydrogel. Taking advantage of both PEG and Col building blocks, the PEG/Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…PEG is highly unstable because of its ether structure, which can form peroxides ( Thoma et al, 2017 ). In view of this shortcoming, PEG can be block copolymerized with other polymers or grafted to slow down the degradation rate ( Chen et al, 2018 ; Fer et al, 2021 ). Polylactic acid (PLA) is a biodegradable material with good solvent resistance and thermal stability ( Vasilyev et al, 2021 ).…”
Section: Fabrication Strategy Of Peg-based Hydrogelsmentioning
confidence: 99%
“…PEG is highly unstable because of its ether structure, which can form peroxides ( Thoma et al, 2017 ). In view of this shortcoming, PEG can be block copolymerized with other polymers or grafted to slow down the degradation rate ( Chen et al, 2018 ; Fer et al, 2021 ). Polylactic acid (PLA) is a biodegradable material with good solvent resistance and thermal stability ( Vasilyev et al, 2021 ).…”
Section: Fabrication Strategy Of Peg-based Hydrogelsmentioning
confidence: 99%
“…These results imply that these tough hydrogels are as tough as natural rubbers [ 83 , 88 , 89 , 90 ]. Many synthetic and natural polymers are used in the preparation of these tough hydrogels such as poly(vinylpyrrolidone) [ 91 ], poly(acrylamide) [ 92 ], poly(acrylic acid) [ 93 ], poly( N -isopropylacrylamide) [ 94 , 95 ], poly(2-acrylamido-2-methylpropanesulfonic acid) [ 82 ], poly(ethylene glycol) [ 96 ], alginate [ 83 ], agarose [ 97 ], and chitosan [ 98 ]. The first generation of double network (DN) hydrogels as reported by Gong and co-workers utilized covalent crosslinkers.…”
Section: Tough Hydrogels With Excellent Load-bearing Performancementioning
confidence: 99%
“…Chen et al fabricated a series of PEG/collagen (PEG/Col) DN hydrogel with significantly enhanced strength and toughness. The results indicated that the PEG/Col DN hydrogels possessed a favorable biocompatibility with a strengthened skeleton, providing an appropriate environment for cell growth in load‐bearing tissue repairing (J. X. Chen et al, ). These approaches would bring DN hydrogels into bone restoration and hard tissue replacement.…”
Section: Dn Hydrogels For Tissue Engineeringmentioning
confidence: 99%